Implementation and evaluation of the public health emergency response to the 2019 outbreak of e-cigarette and vaping product use–associated lung injury in Massachusetts, USA. (March 2022) - Kephart, L.; Rastogi, R.; Song, G.; Ursprung, W.W.S.; Kingsley, M.; Bharel, M.
Abstract: Objectives: In 2019, an outbreak of e-cigarette/vaping product use–associated lung injury (EVALI) across the United States was responsible for acute harm, hospitalizations, and mortality among individuals using vape products, including youth and young adults. The objective of this study is to describe and evaluate the public health surveillance and emergency response activities that occurred in Massachusetts during the 2019 EVALI outbreak. Study design: Descriptive process and policy evaluation. Methods: Between September and December 2019, the Massachusetts Department of Public Health temporarily removed access to e-cigarettes in stores, conducted tobacco retailer educational activities, and promoted tobacco cessation communications. The public health response was monitored through online adult panel surveys, in-school youth surveys, retailer compliance checks, and existing tobacco control program surveillance. Results: Massachusetts residents indicated high awareness of the EVALI outbreak and the corresponding public health response. Tobacco retailers were compliant with the temporary state prohibition on the sale of e-cigarettes. In response to reduced access to vaping products in stores, both adult and youth survey respondents reported reduced use, increased quit attempts, or complete e-cigarette cessation. Conclusion: Emergency action undertaken by state public health programs and other governmental agencies corresponded with reduced availability of e-cigarettes and an increase in self-reported quit behaviors. Existing public health infrastructure at the state and local levels in Massachusetts facilitated an environment in which emergency and permanent protective measures could be implemented.